2002
DOI: 10.1039/b202693g
|View full text |Cite
|
Sign up to set email alerts
|

Radiological study of exposure levels in El Maghara underground coal mine

Abstract: Coal is largely composed of organic matter, but it is the inorganic matter in coal minerals and trace elements that have been cited as possible causes of health, environmental and technological problems associated with the use of coal. Some trace elements in coal are naturally radioactive. These radioactive elements include uranium (U), thorium (Th) and their numerous decay products, including radium (Ra) and radon (Rn). Although these elements are less chemically toxic than other coal constituents, such as ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…Other investigation of the The world range of mineral soil (Parinson and Quamby 1974) is also given Fig. 2 Dendrogram of coal, sludge, waste, and charcoal as a function of Euclidean distance calculated using all measured concentrations of major and trace elements same mine (Amer et al 2002) reported concentration ranges for 226 Ra, 232 Th, and 40 K of 6-22.9, 9.6-47.3, and 77-489 Bq kg −1 , respectively, in the soil-coal dust collected from the gallery. The activity concentrations in sludge and waste are higher than that in extracted coal.…”
Section: Concentrations Of Major and Trace Elements: Cement Plantmentioning
confidence: 99%
“…Other investigation of the The world range of mineral soil (Parinson and Quamby 1974) is also given Fig. 2 Dendrogram of coal, sludge, waste, and charcoal as a function of Euclidean distance calculated using all measured concentrations of major and trace elements same mine (Amer et al 2002) reported concentration ranges for 226 Ra, 232 Th, and 40 K of 6-22.9, 9.6-47.3, and 77-489 Bq kg −1 , respectively, in the soil-coal dust collected from the gallery. The activity concentrations in sludge and waste are higher than that in extracted coal.…”
Section: Concentrations Of Major and Trace Elements: Cement Plantmentioning
confidence: 99%
“…One working level represents any combination of short-lived radon daughters' concentration in 1 l of air that results in the ultimate emission of 1:3 Â 10 5 MeV of alpha energy, taking no account of the radon (Amer et al, 2002). Thoron ( 220 Rn) progeny concentrations were measured using Rock method (Rock, 1975).…”
Section: Experimental Workmentioning
confidence: 99%
“…It has been indicated that 222 Rn gas (a decay product of 238 U-226 Ra series) and its progeny constitute the largest single contributors to human radiation exposure from natural and man-made radioactive sources (UNSCEAR, 1988(UNSCEAR, , 1977. Inhalation of radon and its short-lived decay products constitutes the most important occupational exposure of workers in mines (Amer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies had been performed in order to explore the problem and to found parameters that could be used in risk assessment models [1][2][3][4]. The goal of this paper is to explore the impact of the coal mines Tusnica which has slightly rising levels of natural radionuclides 238 U and 226 Ra into acoount the risk for population and for environment.…”
Section: Introductionmentioning
confidence: 99%